Hubungan Tekanan Teman Sebaya dengan Perilaku Cybersex pada Remaja - Raudatul Hulma; Maya Yasmin (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
This study aims to determine the relationship between peer pressure and cybersex behavior in adolescents. This study used a correlational quantitative approach with 270 subjects aged 15-19 years, which were determined by snowball sampling technique. The measuring instruments used were the Cybersex Scale and the Peer Pressure Scale compiled by researchers based on aspects of Delmonico & Miller (2003) and Kiran-Esen (2003). Data analysis using product-moment correlation resulted in a hypothesized correlation coefficient of 0.700, P = 0.000 (p < 0.05) indicating that there is a positive relationship between peer pressure and cybersex behavior in adolescents.